2016
DOI: 10.1371/journal.pone.0167013
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Urinary Excretion of Trimethylselenonium and Trimethylsulfonium in Humans

Abstract: Hydrogen sulfide is a signaling molecule that plays important roles in several physiological processes, and its methylation product trimethylsulfonium (TMS) is a natural constituent of human urine that could serve as a biomarker for hydrogen sulfide. In vitro studies showed that the enzyme indole-ethylamine N-methyltransferase (INMT) is responsible for the production of trimethylsulfonium as well as its selenium analogue trimethylselenonium (TMSe). Marked inter-individual variability in TMSe production is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…TMSe is produced following methylation of hydrogen selenide first to methylselenol (driven by thiopurine S ‐methyltransferase (TPMT)), then to DMSe (driven by either TPMT or indolethylamine N ‐methyltransferase (INMT)) and finally to TMSe (driven by INMT). A genetic polymorphism in the human INMT gene results in the fact that some individuals are not able to excrete TMSe in substantial amounts (TMSe non‐eliminators) (Lajin and Francesconi, 2016 ). It has been suggested that conversion of hydrogen selenide to methylselenol and to DMSe takes place in the liver, while the urinary metabolite TMSe is produced from DMSe in the lungs (Fukumoto et al., 2020 ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…TMSe is produced following methylation of hydrogen selenide first to methylselenol (driven by thiopurine S ‐methyltransferase (TPMT)), then to DMSe (driven by either TPMT or indolethylamine N ‐methyltransferase (INMT)) and finally to TMSe (driven by INMT). A genetic polymorphism in the human INMT gene results in the fact that some individuals are not able to excrete TMSe in substantial amounts (TMSe non‐eliminators) (Lajin and Francesconi, 2016 ). It has been suggested that conversion of hydrogen selenide to methylselenol and to DMSe takes place in the liver, while the urinary metabolite TMSe is produced from DMSe in the lungs (Fukumoto et al., 2020 ).…”
Section: Assessmentmentioning
confidence: 99%
“…The excretion of DMSe in breath and TMSe in urine has been proposed to reflect processes that aim at minimising selenium accumulation in the body outside the regulated pool (Burk and Hill, 2015 ). Notably, as described in Section 3.2 , TMSe excretion is influenced by a polymorphism in the INMT gene, which characterises individuals as eliminators or non‐eliminators of TMSe, and eliminators may excrete TMSe in urine at usual dietary selenium intakes (Lajin and Francesconi, 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Elevated levels of these volatile compounds can lead to expiration from the lung and skin, and a garlic-odored breath associated with selenium (Se) toxicity (selenosis) and tellurium toxicity [47]. Methylation of DMS, DMSe and DMTe yields the positively charged non volatile trimethylated products trimethylsulfonium (TMS), trimethylselenonium (TMSe) and trimethyltelleronium (TMTe), essential for urinary excretion [8–10]. Recent work has shown that human INMT (hINMT) can methylate dialkylthiols [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated significant inter-individual variability in the production of TMS. Trimethylsulfonium and TMSe are known to be produced by the same enzyme thioether S-methyltransferase (12), which is encoded by the INMT gene, and this gene has been found to be genetically polymorphic, with a strong impact reported on TMSe production (23,24). It is therefore likely that the genetic polymorphisms in the INMT gene can impact the production of TMS and result in significant inter-individual variability.…”
Section: The Variability In the Human Urinary Excretion Of Trimethyls...mentioning
confidence: 99%